Fostering Inclusivity: Adjusting Learning Methods to Students with Impaired Hearing at SLB Ma’arif NU Lamongan - Wahyudi, Winarto Eka; Masuwd, Mowafg Abrahem (Didaktika Religia, 2024)
Every child possesses an equal entitlement to receive high-quality education, including those with auditory impairments. Delivering Islamic education to these students poses distinctive challenges, necessitating a tailored instructional approach. SLB Ma’arif NU Lamongan is committed to student diversity and implements a unique learning strategy to cater to the educational requirements of its hearing-impaired students within the Islamic education framework. This study focuses on the methodologies and tactics employed bhy the school to address varied learning needs. Employing a qualitative research methodology, it incorporates observations, in-depth interviews with educators and administrative personnel, and analysis of curriculum documents. Thematic analysis is utilized to discern recurring patterns and themes pertaining to the execution of the learning approach. SLB Ma’arif NU Lamongan adopts a differential learning model to accommodate the diverse requirements of students with impaired hearing in Islamic education through customizing lesson plans tailored to individual impairment levels, leveraging sign language and assistive technologies, and deploying both individualized and collaborative learning strategies. The school also cultivates an inclusive educational milieu conducive to the spiritual, cognitive, and emotional development of its learners. This research contributes to elucidating the significance of adapting instructional methodologies to address diverse learning needs and cultivating an inclusive learning environment to ensure equitable educational opportunities for all students, irrespective of their auditory capabilities.